English Language Teaching in India: Challenges and Trends - Subramanian, Lakshmi (Integrated Journal for Research in Arts and Humanities, 2023)
The ‘English-speaking culture’ is deep-rooted in India and its dominancy initiated when language imperialism started along with the aggressive colonial rule. India is a land of diverse cultures, heritage and languages with about 19,500 regional languages and dialects. Various regional challenges associated with the process of teaching English have been discussed in this paper.